2022
DOI: 10.3389/fphar.2022.954030
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Tamarindus indica and Coenzyme Q10 can be a Potential Therapy Preference to Attenuate Cadmium-Induced Hepatorenal Injury

Abstract: Cadmium (Cd) is a hazardous environmental pollutant that menaces human and animal health and induces serious adverse effects in various organs, particularly the liver and kidneys. Thus, the current study was designed to look into the possible mechanisms behind the ameliorative activities of Tamarindus indica (TM) and coenzyme Q10 (CoQ) combined therapy toward Cd-inflicted tissue injury. Male Wistar rats were categorized into seven groups: Control (received saline only); TM (50 mg/kg); CoQ (40 mg/kg); Cd (2 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As a consequence, tubular dysfunction occurs and is demonstrated by a significant upsurge in the serum levels of urea, creatinine, and uric acid. These results support our preceding research, which revealed a positive association between the MDA level and the increased serum levels of renal function parameters (Abdelnaby et al, 2022). Our findings are in agreement with those of Manafi (2018) who reported that the albumin level is negatively affected when Japanese quails are treated with AFT.…”
Section: •-supporting
confidence: 93%
See 1 more Smart Citation
“…As a consequence, tubular dysfunction occurs and is demonstrated by a significant upsurge in the serum levels of urea, creatinine, and uric acid. These results support our preceding research, which revealed a positive association between the MDA level and the increased serum levels of renal function parameters (Abdelnaby et al, 2022). Our findings are in agreement with those of Manafi (2018) who reported that the albumin level is negatively affected when Japanese quails are treated with AFT.…”
Section: •-supporting
confidence: 93%
“…Additionally, GSH plays a crucial role as a co-substrate for enzyme GPx, which is in charge of detoxifying the H 2 O 2 and lipid hydroperoxides, as well as direct neutralization of AFT (by forming an AFT–GSH conjugation) ( Kemal and Seker, 2023 ). However, Fenton’s reaction is initiated when antioxidants are depleted by AFT-initiated ROS; therefore, enormous amounts of OH • are built up, which aggressively attack the phospholipid membrane, leading to MDA accumulation ( Aboubakr et al, 2021 ; Abdelnaby et al, 2022 ). MDA is the byproduct of lipid peroxidation (LPO) that represents the degree of membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when CAT is dwindling, an iron-catalyzed Haber–Weiss reaction (H 2 O 2 + Fe 2+ → OH • + OH − + Fe 3+ ) generates extremely harmful reactive OH • radicals that can directly damage the membrane lipids, triggering LPO with a further generation of another harmful substance, MDA (an LPO biomarker) ( Giuranno et al, 2019 ; Abdelnaby et al, 2022 ). Even worse, MDA itself could interact with other key biomacromolecules, resulting in extensive cellular damage ( Abdelnaby et al, 2022 ). Current investigation revealed substantial increases in MDA levels, confirming the possibility of membrane insult following IR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, our present study elucidated that oxidative stress was crucial in the lingual damage caused by IR, indicated by the decline of the SOD and CAT activities, alongside the TAC level, in the tongue of exposed rats. SOD is an endogenous enzyme serving as the first line of defense that swiftly catalyzes the dismutation of O 2 (Giuranno et al, 2019;Abdelnaby et al, 2022). Even worse, MDA itself could interact with other key biomacromolecules, resulting in extensive cellular damage (Abdelnaby et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants of plant origin have garnered global attention recently and are frequently used due to their phytochemical content [ 18 ]. Among them, nootkatone (NK; C 15 H 22 O) is a sesquiterpenoid extracted from several plants including grapefruit and rhizomes of Cyperus rotundas , as well as essential oil derived from citrus [ 19 ].…”
Section: Introductionmentioning
confidence: 99%